ANALISA MANAJEMEN KEUANGAN DAN STRATEGI PENGEMBANGAN CAFÉ ABC - Nunuk Novianti; Wizanasari Wizanasari (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The purpose of this research is to analyze the financial management and marketing mix strategy by Café ABC in the development of Cafe as an implication of management policy. The research method used is quantitative for financial management analysis with parameters Margin Contribution, Break Event Point, Margin of Safety, Shut Down Point, and Degree of Operating Leverage. And a qualitative method for formulating strategies with IFE and EFE matrix parameters, SWOT matrix, IE matrix and QSPM as decision making. The data used in this study are primary data sources obtained from interviews with company managers. Secondary data is obtained from the financial and operational reports of the Café every month, as well as data from the relevant literature. From the results of the financial management analysis, it shows that the difference between income and costs from individual guests is positive, so that activities to separate individual guests from group guests can continue. The results of the IE matrix show that Cafe is in a growth and build position with an intensive strategy, namely market penetration strategy, market development and product development. The results of the QSPM include the main alternative strategy with the highest TAS value of 5,761, the S-O strategy ranks third with a TAS value of 4,932 and the sixth with a TAS value of 3,724. The S-T strategy ranks seventh with a TAS value of 3,515, W-O strategy with a TAS 5,534 value, the strategy for optimizing development is fifth with a TAS value of 3,804 and a faster return on profits for group guests of Rp. 59,163,725,- W-T strategy obtained TAS value of 5,761 with the largest contribution profit value for group guests of Rp. 186.033,244,-